Avaliação das atividades de controle da leishmaniose visceral na Regional Noroeste de Belo Horizonte, 2006 a 2010 - Maria Helena Franco Morais (2011)
American visceral leishmaniasis (AVL) has become one important infectious diseases. The disease control has been hampered by different issues, as the process of urbanization and the occurrence of co-infections, which makes the cases worse. Control measures used until now, have enabled the spread of the disease increasingthe number of cases. Considering these issues, this study aimed to evaluate the LV control actions in the NorthWest Regional (NO) of Belo Horizonte, Minas Gerais, Brazil, as well as the impact obtained by these actions and their implementation, from 2006 until 2010. Indicators were proposed to evaluate the adequacy and effectiveness of different strategies of the Program for the Control of Visceral Leishmaniasis (PCLV). It was verified if the valuation model used subsidized the formative and summative assessment of the different phases of PCVL in urban areas. This study was conducted with two designs. The descriptive analysis evaluated the adequacy of activities considering the impact indicators trends. Data from control actions for the reservoir andvector were used. It was obtained from the Information System for Zoonoses Control, and human cases´s data were obtained from the National Information System of Notifiable Diseases. A quasi-experimental study was conducted in three areas withcontrol area, and differentiated time of activities control intervention were used to evaluate the effectiveness. The prevalence of human infection and the risk variables associated with the infection were assessed by a cross-sectional study with a serological survey of 1875 children up to eight years old, living in these three areas. Blood samples collected on filter paper were examined by enzyme linked immunosorbent assay ELISA with L. infantum crude antigen and rk39 recombinante antigen as well as by direct agglutination test (DAT). The positive samples and 15% of randomized selected negative samples were submitted to molecular diagnosis by real time PCR. In a second step, one year after the first collection, reactive´s children were re-examined. Clinical examination was included in this stage, with an infectious disease doctor. The prevalence of infection varied according to the diagnostic technique used.Considering all serological techniques (ELISA AgT and rK39, and DAT), 17.1% of children were reactive. Among these techniques, ELISA with rK39 was the most reactive and better reproducibilited assay, with 14.9% (13.4-16.6) of reactivity. The infection rate by qPCR was 14.7%. There was no correlation between the techniques used and, the prevalence, considering all reactive children in at least one test was 30.8%. The results obtained with rK39 ELISA were used in a mixed-effects multivariate logistic analysis as the marker of infection. Variables relating to household were associated with infection: houses with roof and without a full slab, and walls without mortar increased the chance of infection in children by 1.6 times (OR 1.6 95% 1.0 to 2.4) and (OR 1.6 95% 1.0 to 2.3) respectively. Children, who were living in the areawith a longer intervention, since 2006, had a reduced infection chance in 40% when compared to the control area. No child developed clinical form of AVL. The results of the indicators showed significant progress in the adequacy of control activities, but monitoring is important, requiring the adaptation of the vector control activity with main regard to it´s productivity and frequency, according the guidelines PCLV / MS. There was a reduction of 33.3% in the canine positivity from the area with intervention since 2006 and 47.7% in the area worked since 2008. In the NO, this reduction was 49.5%. There was no difference in this indicator between selected areas for the cross-sectional study in canine serological surveys conducted in 2010, demonstrating the comparability of these areas. The evaluation process also identified considerable disagreement between the diagnostic techniques used in canine surveys, which may have reduced the impact of this strategy. The incidence of AVL ranged from 29.0 (6 cases) per 100 000 inhabitants in 2006 to zero in the year 2010, in the area with a longer intervention. In the area where the activities were initiated in 2008, the values ranged from 8.9 (two cases) to 4.4 per 100 000 inhabitants. The control area showed only one case during this period. The evaluation of the indicators showed the effectiveness of control strategies, however, the diagnostic techniques used need to be reviewed, both for the reservoir control and for the human infection study.